Cardioprotective activity of Apples Juice on Isoproterenol-Induced Myocardial Infarction in Rat - Kurniati, Neng Fisheri; Nadhirah, Yuthika Raihan (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Myocardial infarction was local necrosis of heart tissue due to reduced oxygen supply because of theocclusion of coronary arteries. Fruits could reduce the risk of developing obesity and CVDs. Severalstudies have shown that apples had a strong cardioprotective effect. This study aimed to understandthe cardioprotective activity of two variants of apples, e.g., Fuji and Malang, on isoproterenol-inducedmale Wistar rats. The cardioprotective activity test was carried out for 14 days, all testing group exceptnegative control, was induced by isoproterenol. The results of testing cardioprotective activity showedthat Fuji Apple juice and Apel Malang juice had the same capability to inhibit increasing cardiacbiomarkers value (CK and CK-MB) with the highest inhibition was 79.56% and 73.08% for FujiApples, respectively, while for Apel Malang was 69.18% and 43.04%, respectively. The result of thecardiac histopathology examination showed that both Apples could prevent cardiac tissue damage. Alljuice Apple doses had the same cardioprotective activity.